2019
DOI: 10.1158/1078-0432.ccr-18-3642
|View full text |Cite
|
Sign up to set email alerts
|

Carfilzomib Weekly plus Melphalan and Prednisone in Newly Diagnosed Transplant-Ineligible Multiple Myeloma (IFM 2012-03): A Phase I Trial

Abstract: Purpose: Carfilzomib is a novel generation proteasome inhibitor. The Carmysap trial demonstrated that twice-weekly KMP (carfilzomib, melphalan, prednisone) might challenge the MPV (melphalan, prednisone, bortezomib) standard. We sought to study KMP weekly, allowing to increase carfilzomib's dose with maintained efficacy and improved safety profile. Patients and Methods: IFM2012-03, a phase I multicenter study of KMP weekly in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Carfilzomib, Melphalan, and Prednisone (CMP) IFM 2012-03, a phase I trial by Leleu et al, 2019 27 studied the role of weekly CMP in 30 transplant-ineligible elderly NDMM patients (median age=73 years; high-risk cytogenetics, n=3) and determined the MTD of CFZ. Patients underwent nine 35-day cycles of CMP induction with CFZ given in four intravenous dosing cohorts [36 mg/m 2 (n=6), 45 mg/m 2 (n=6), 56 mg/m 2 (n=6), and 70 mg/m 2 (n=12)] followed by CFZ maintenance for 1 year (36 mg/m 2 every 2 weeks).…”
Section: Dovepressmentioning
confidence: 99%
“…Carfilzomib, Melphalan, and Prednisone (CMP) IFM 2012-03, a phase I trial by Leleu et al, 2019 27 studied the role of weekly CMP in 30 transplant-ineligible elderly NDMM patients (median age=73 years; high-risk cytogenetics, n=3) and determined the MTD of CFZ. Patients underwent nine 35-day cycles of CMP induction with CFZ given in four intravenous dosing cohorts [36 mg/m 2 (n=6), 45 mg/m 2 (n=6), 56 mg/m 2 (n=6), and 70 mg/m 2 (n=12)] followed by CFZ maintenance for 1 year (36 mg/m 2 every 2 weeks).…”
Section: Dovepressmentioning
confidence: 99%
“…KMP has proven to be safe and effective in NDMM 110,111 . The CLARION trial compared transplant ineligible patients receiving KMP versus VMP and found that KMP did not improve PFS as compared to VMP (22.3 months vs. 22.1 months, HR = 0.906, 95% CI: 0.74–1.1); suggesting that carfilzomib in combination with melphalan might not be a good option for NDMM 112 …”
Section: Treatment Of Ndmmmentioning
confidence: 99%
“…In a preclinical model, carfilzomib showed a stronger anti-myeloma effect than bortezomib. In addition, this new generation proteasome inhibitor has a different safety profile than bortezomib, showing a very low incidence of neuropathy [ 84 ]. The side effects of drugs were described in the phase III ENDEAVOR clinical trial.…”
Section: Clinical Usage Of Combination Treatment With Melphalan To Improve the Effectiveness Of Cancer Therapymentioning
confidence: 99%